African-American women's attitudes and expectations of menopause - Holmes-Rovner, M; Padonu, G; Kroll, J; Breer, L; Rovner, D R; Talarczyk, G; Rothert, M (American journal of preventive medicine, 1996)
In this study, low-income perimenopausal African-American women were surveyed to determine knowledge of menopause and hormone replacement therapy (HRT). A 92-item survey assessed perceptions of menopause and health risks to identify preventive strategies in this population. The nonprobability sample of 197 African-American women typically had incomes of < $15,000, age 46-55, high school education or less. Major findings were that African-American women (1) experienced expected levels of occurrence of symptoms, but perceived them as not very bothersome, (2) had a knowledge deficit related to menopause and HRT, and (3) had expectations about menopause that underestimated their lifetime risk of heart disease. The lack of knowledge about menopause, HRT, and lifetime risks of heart disease suggests that low-income African-American women need better information for decision making about prevention. However, this sample knew the rank order of major health risks. Health information to the public and culturally relevant patient education are critical prerequisites to any preventive behavioral strategies in this population. Further research should identify culturally based expectations of disease risk and efficacy of prevention strategy to tailor messages to particular subpopulations.